’ქიმერების მარულა’ (ფანტასმაგორია‚ მითის კულტი და ანტიკურობა ვალერიან გაფრინდაშვილის შემოქმედებაში) - ტონია ნანა (ლოგოსი, 2022)
The supreme aim of the poetic art lies in its aspiration for imagining visual images of the words. The impression made by the poetic icon/image is defined by the illusion of the secrecy and existence (of the icon). The most important in secrecy is the effect of symbol(ism), which has no effectively been manifested in the creative work of the Georgian modernists. Valerian Gaprindashvili, the most important representative of the Georgian modernism, is not merely a port, but also the ideologist of the poetic reasoning of his era. His essays: “remarks/observation on lyrics”. “Terra Antiqua”, “a New Mythology”, “Elysium of Lyrics” “the Magic of Names”, and etc. can easily be accepted as the manifesto of the Georgian modernism. Modernism in the Georgian poetic reasoning has been introduced in the form of essays, resisting the social pathos characteristic to "Tergdaleuli" publicism. The ideology of modernism inculcated by the poets and writers of a new generation crushed the worlviews, aesthetics and style existing in that era. Though, modernists were under the influence of European and Russian poetry, however, they did not forget the ancient tradition being inherited from the Georgian poetry. The representatives of the Georgian poetry have vigorously welcomed the aspiration for the renewal in every era. It has accepted and internalized the byzantine poetic art and produced brilliant pieces of hagiographic and hymnographic literature; it has accepted the specific eastern style of poetic reasoning, replenishing it own national style, which resulted in a unique masterpiece “The Knight in Panther's Skin”; David Guramishvili should also be specifically mentioned, whose name was reminded by Gaprindashvili to the Georgian society in the vast essay of 1919 ("David Guramishvili"). Gaprindashvili was not a poet for the masses. A specific education and knowledge of versification is needed to comprehend his writings. His essays were also specifically designed for the readers with respective knowledge, since they were rich with analogies, parallels, comparisons, metaphors and etc... The special attitude of the poet towards the myths as well as the historic figures of the ancient world was evident in his writings. During his short lifespan he was constantly engaged in enriching his knowledge and searched for the magic in names, beauty in horror and terror, Apollonian and Dionysian elements in antiquity, and, the spiritual ancestors in the Georgian reality. Valerian Gaprindashvili, a poet possessed with the secret force of poetry, had a sophisticated knowledge in the theory of art preaching “the necessity of phantasmagoria and the cult of myth, for overcoming the narrow margins of reality and ethnography” (essay: “New in the Georgian Poetry of 1922”). His creative work, which is loaded with the reminiscences of the antique world, attracts the attention of the reader with the symbolic interpretations of the images. In Valerian Gaprindashvili’s iconic aesthetics of symbols the idea of myths appearing from symbols can be read, as well the possibility for myth-making, and the perception of the religious nature of the substance of art.